How long after maximal physical exertion should baseline computerized neurocognitive testing and symptom assessment be administered?. (18th January 2021) - Mohler, Samantha; Elbin, R. J.; Ott, Summer; Butts, Cory L.; McDermott, Brendon; Ganio, Matthew S.; Covassin, Tracey
ABSTRACT: Objective : Prior research suggests maximal physical exertion (MPE) may negatively affect the reliability and validity of computerized neurocognitive testing (CNT); the purpose of this study was to identify aclinically relevant recovery interval following MPE for the administration of baseline CNT. Design : Random-crossover. Participants : Thirty (M = 21.87 ± 2.29 y), moderately-active, healthy participants, without history of ADHD, learning disabilities, psychological disorders or concussion (within the last six months). Intervention : Participants completed four randomly ordered experimental trials. Except for the control trial, CNT was administered following MPE with assigned recovery intervals [Immediate, 10-minutes, or 20-minutes]. Aseries of repeated measures analysis of variance (ANOVAs) were performed on CNT composite and total symptom scores. Results : Total symptom scores were significantly greater ( p < .01) at the immediate, 10-minute, and 20-minuterecovery intervals compared to the control trial. Processing speed was significantly faster at the 20-minuterecovery interval compared to the control trials. Visual memory, verbal memory, or reaction time did not differ across recovery intervals. Conclusions : Clinicians should wait more than 20 minutes before assessing baseline concussion symptoms following about of MPE.